2007
DOI: 10.1113/jphysiol.2007.138024
|View full text |Cite
|
Sign up to set email alerts
|

Reorganized stores and impaired calcium handling in skeletal muscle of mice lacking calsequestrin‐1

Abstract: Calsequestrin (CS), the major Ca2+ -binding protein in the sarcoplasmic reticulum (SR), is thought to play a dual role in excitation-contraction coupling: buffering free Ca 2+ increasing SR capacity, and modulating the activity of the Ca 2+ release channels (RyRs). In this study, we generated and characterized the first murine model lacking the skeletal CS isoform (CS1). CS1-null mice are viable and fertile, even though skeletal muscles appear slightly atrophic compared to the control mice. No compensatory inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
244
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(269 citation statements)
references
References 78 publications
(80 reference statements)
24
244
1
Order By: Relevance
“…The absence of an effect on depolarizationinduced Ca 2+ release in pan-triadin knockout mice could result from a multitude of different compensatory mechanisms commandeered to correct for the loss of a critical RyR1 regulatory protein. In fact, skeletal muscle function and EC coupling is also not markedly altered following knockout of the skeletal muscle isoform of calsequestrin (CSQ1; Paolini et al, 2007). Similarly, cardiac SR Ca 2+ storage and depolarization-induced Ca 2+ release are essentially normal following either global knockout of CSQ2 (Knollmann et al, 2006) or cardiac-specifi c knockout of the Na/Ca exchanger (Henderson et al, 2004), respectively.…”
Section: -232) (mentioning
confidence: 87%
“…The absence of an effect on depolarizationinduced Ca 2+ release in pan-triadin knockout mice could result from a multitude of different compensatory mechanisms commandeered to correct for the loss of a critical RyR1 regulatory protein. In fact, skeletal muscle function and EC coupling is also not markedly altered following knockout of the skeletal muscle isoform of calsequestrin (CSQ1; Paolini et al, 2007). Similarly, cardiac SR Ca 2+ storage and depolarization-induced Ca 2+ release are essentially normal following either global knockout of CSQ2 (Knollmann et al, 2006) or cardiac-specifi c knockout of the Na/Ca exchanger (Henderson et al, 2004), respectively.…”
Section: -232) (mentioning
confidence: 87%
“…6b). The dots are clearly not composed of CASQ1, a protein that is totally absent in these fibers (Paolini et al 2007). The SR aggregates in CASQ1-null fibers seem to be a repetition of this structure in the sense that small dense dots are present inside each circular sectioned tubule profile and that the size of the circles is similar to the scallops in the jSR.…”
Section: Resultsmentioning
confidence: 99%
“…Significant differences were observed for the functional output, as the grip strength test revealed that untrained CASQ1-null mice were about 60% weaker than age-matched WT at both 2 and 4 months of age. On the other hand, the maximum speed reached during the incremental test was surprisingly higher in CASQ1-null mice: this last result is likely due to the increased number and volume of mitochondria in CASQ1-null muscles (see below; see also [27]). Two months of aerobic training (2 to 4 months of age; see Figure 1), while did not change the average body weight of CASQ1-null mice, significantly improved both functional parameters: (a) the grip strength output normalized by weight increased from 3.0 ± 0.8 g/g of body weight in untrained CASQ1-null to 4.8 ± 1.1 g/g of body weight in trained CASQ1-null and (b) the maximum speed reached during the incremental test was slightly higher in trained than in untrained CASQ1-null mice, respectively, 32.5 ± 3.9 versus 28.1 ± 2.7 m/min.…”
Section: Aerobic Training Increased Functional Output Andmentioning
confidence: 91%
“…CASQ1-null mice were generated as previously described [27]. All animals used in this study were males, as this gender is more susceptible to MH/ EHS-like crises when exposed to halothane and heat [22].…”
Section: Casq1-null Malementioning
confidence: 99%
See 1 more Smart Citation